Bridging high pressure rheology and film-forming capacity of polymer-base oil solutions in EHL. (January 2016) - Mary, C.; Philippon, D.; Devaux, N.; Fillot, N.; Laurent, D.; Bair, S.; Vergne, P.
Abstract: The development of high value-added lubricants which overcome more drastic operating conditions, are fuel-efficient and provide excellent performance for a long life remains a huge challenge for oil makers. This article sheds light on the tribological response of an EHD circular rolling–sliding contact for a base oil and three polymers mixed in solutions in order to understand the relationship between physico-chemistry and tribology. The final aim is to help formulators select the appropriate chemicals meeting engine specifications. Central and minimal film thickness measurements were run on a ball-on-disc tribometer and determined through white light optical interferometry. Experiments were compared with classical analytical predictions and with the results of a finite element numerical solver based on the generalized Reynolds' equation including the modelled rheological behavior established from high-pressure and high-stress viscosity measurements and density variations. Moreover, the role played by thermal effects and variable slide-to-roll ratio were discussed. Highlights: We measured the tribological response of an EHD circular rolling–sliding contact. Several simplified automotive lubricants were studied (three polymers mixed in a base oil). Film thicknesses were measured on a ball-on-disc tribometer through white light optical interferometry. Experiments were compared with the results of a finite element numerical solver based on the generalized Reynolds' equation. Thermal effects and variable slide-to-roll ratio were discussed.